DEVELOPING TOLERANCE ATTITUDES OF STUDENTS OF DIFFERENT RELIGIONS BASED ON MULTICULTURALISM THROUGH HABITS AT SDN 094123 SORDANG BOLON - Nabelia Utami Manurung; Yakobus Ndona; Ibrahim Gultom (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this research is the importance of developing multiculturalism attitudes through habits, especially in SDN Sordang Bolon. The research method used is a qualitative research method of case study type. Data using data reduction, namely summarizing important things related to existing phenomena. The result of the research is that tolerance based on multiculturalism through habits, becomes a way to develop tolerance attitudes of students of different religions. The importance of practicing tolerance in the life of the nation and state, because every individual or group comes into contact with people of different backgrounds. Therefore, in this case it is very important to frame the role of multiculturalism through, especially in formal education, in the attitude of tolerance.